Interruptions in administration of enteral feeding and automatic compensation: A post hoc analysis of the smART+ study - I. Kagan; E. Robinson; M. Hellerman Itshaki; P. Singer (Clinical Nutrition Open Science)
Summary: Rationale: Multiple obstacles exist to achieve enteral feeding targets defined as patient-related (PR) or diagnostic/therapeutic related (DTR) interruptions. A new technology was developed to adapt and compensate enteral feeding according to gastric tolerance as well as DTR interruptions (1). In this post hoc analysis we evaluated PR or DTR interruptions as well as the compensation achieved by the platform. Methods: The compensation related to PR or DTR was analyzed in 50 patients from the study group (1). A computerized analysis detected all the PR and DTR interruptions. Analysis used only those days with at least 12 hours of active system. Compensation was programmed to provide 100 % of the missing nutrition related to DTR interruptions and 50 % of the measured gastric active residual release (ARR). Results: 280 days were obtained with at least 12 hours of recording from the 313 hospitalization days. Interruptions occurred during 4.5 hours in mean. A total median of 75 min (19.5 % of the interruption time) was related to PR and a total median of 196 min (80.5 %) to DTR interruptions. However, the feeding efficacy remained very high (89,3 %) during the study period. Nutritional therapy close to 100 % of the target was obtained in 176 days out of the 280 investigated days. Conclusion: Interruptions of enteral feeding were mainly related to DTR interventions, but the platform was able to fully compensate for them. The PR interruptions were only partially compensated. The smart + platform provides an effective tool to recognize feeding interruptions and to compensate them.